"In rape cases we can use this pill": A multimethods assessment of emergency contraception knowledge, access, and needs on the Thailand − Burma border. (31st May 2015) - Hobstetter, Margaret; Sietstra, Cari; Walsh, Meredith; Leigh, Jennifer; Foster, Angel M.
Abstract: Objectives: To evaluate availability, service delivery, and barriers to access to emergency contraceptive pills (ECPs) along the Thailand–Burma border. Methods: From June 2010 to May 2011 we undertook a multimethods qualitative assessment among cross‐border populations, migrants, and refugees. We conducted 46 key informant interviews with representatives from 25 organizations, 18 focus group discussions with migrant adults, migrant adolescents, and healthcare workers, and a service mapping exercise with 22 stakeholders. Results: We found low use of ECPs among the target populations. Structural barriers and lack of evidence‐based reproductive health protocols, education, and information restrict access to the limited family planning resources available in this region. Misinformation about ECPs was widespread among health workers and organizational policies were often non‐evidence based. Conclusion: Potential policy and program interventions to improve access to ECPs along the Thailand–Burma border include integrating evidence‐based practices into community efforts, expanding training opportunities for health workers, and improving communication and coordination among organizations serving populations on both sides of the border.